Political Covenants, Treaties, and Loyalty Oaths in Babylonia and between Assyria and Babylonia - Brinkman, J.A.
includes an appendix: The Text of the Treaty between Marduk-zakir-shumi I and Shamshi-Adad V, with an handcopy, translit. and transl., of Rm. 2,427; cf. 50:1442, Text No.1